2009
DOI: 10.1182/blood-2009-03-208181
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of endogenous tumor-associated regulatory T cells improves the efficacy of adoptive cytotoxic T-cell immunotherapy in murine acute myeloid leukemia

Abstract: IntroductionAcute myeloid leukemia (AML) with unfavorable cytogenetics has a poor outcome, even when treated with aggressive chemotherapy. 1,2 With chemoradiotherapy and hematopoietic stem cell transplantation, a graft-versus-leukemia effect can be observed even in patients with unfavorable cytogenetics. 3 Although donor lymphocyte infusion (DLI) given as adoptive immunotherapy after hematopoietic stem cell transplantation has improved the outcomes of certain types of leukemia, 4-6 for patients with AML, DLI h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
116
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(119 citation statements)
references
References 54 publications
3
116
0
Order By: Relevance
“…8 Hallet et al analyzed the efficacy of NK cells in a murine adoptive transfer model in which Tregs were depleted with an anti-CD25 antibody.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8 Hallet et al analyzed the efficacy of NK cells in a murine adoptive transfer model in which Tregs were depleted with an anti-CD25 antibody.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 However, we acknowledge that the absence of donor NK cells in patients is likely the consequence of a variety of rejection mechanisms. 8,[22][23][24][25] Direct NK-cell inhibition via Treg membrane-bound transforming growth factor-b has been reported and may also contribute suppression of in vivo NK-cell expansion. 26 Targeting some proposed inhibitory mechanisms such as blockade of cytotoxic T-lymphocyte antigen 4, the programmed cell death protein 1 pathway, or inhibitors of indoleamine 2,3-dioxygenase may further unleash suppressed NK-mediated immunity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…69 Data from mouse models is somewhat contradictory; tumor regression after IL-2-diphtheria toxin-mediated Treg depletion was seen in one model suggesting that Tregs may adversely affect disease-control. 70 In contrast, simultaneous adoptive transfer of Tregs and unselected donor T-cells in mismatched mouse transplant models showed protection from GvHD without impairing tumor control. 71,72 It has been suggested that this apparent specificity of Tregs for alloreactive T-cells rather than tumor-reactive T-cells may relate to a different mechanism for the development of GvHD and GVL effect.…”
mentioning
confidence: 99%
“…Because IDO can be induced by IFN-g, IDO-negative cancer cells may be initiated to express IDO when exposed to an inflammatory context in the tumor microenvironment, and thereby hinder CD8 þ T-cell-mediated tumor regression before it can be effective (4,5,12). Recently, strong evidence has indicated that modification of the tumor microenvironment, such as the blockade of the TGF-b signaling pathway (15,16), inhibition of IDO (17,18), or depletion of Tregs (19,20) is able to augment the cytotoxicity of CD8 þ T cells.…”
Section: Introductionmentioning
confidence: 99%